CAUSAL MODELS FOR MONITORING THE PROGRESS OF INFANTS WITH LOW BIRTHWEIGHT - LONGFORD, Nicholas Tibor; RAMIREZ, Oscar; GIFFE, Cindy (Brazilian Journal of Biometrics, 2017)
We study the weight (body mass) of infants born prematurely and with low birthweight during the first postnatal year. The infants are enrolled in the Casa Canguro programme in Valle de Cauca, a department (province) of Colombia. The current weight and other physiological measurements are recorded at their visits to participating health-care facilities. We compare two groups of infants: those born at 31 weeks of gestational age or earlier (extremely preterm) and those born at 33 weeks or later (preterm). The comparisons are made using the potential outcomes framework, regarding the two groups as treatments and selecting from them pairs matched on an extensive set of covariates. Matching is accomplished by propensity scoring. The outcomes (weight and height) at a particular age are approximated by interpolation. We conclude that the average weight-handicap of the extremely preterm infants first increases, from about 600 grams at birth to 900 grams on average at three months, and then is reduced, so that by the first birthday they are only about 250 grams lighter on average.